Distributed Localization Algorithm Using Hybrid Cuckoo Search with Hill Climbing (CS-HC) Algorithm for Internet of Things - Kesavan, S.P.; Sivaraj, K.; Palanisamy, A.; Murugasamy, R. (International Journal of Psychosocial Rehabilitation, 2019)
Currently, Internet of Things (IoT) influenced applications are significant upon deployed sensors accurately. Anyhow, classical optimization problem is induced along NP-hard class of problems to determine the accurate localization of deployed sensors nodes. Thence this proposal work provides distributed localization algorithm using hybrid Cuckoo search with hill climbing (CS-HC) algorithm. In turn it improvises the mechanism of optimisation solution by validating threshold value for IoT. Computational complexity get reduced by locating deployed sensor nodes via CS-HC algorithm as well as increase lifetime of resource constrained IoT sensor nodes. Simulated results predicts that proposed CS-HC algorithm produces significant performance accurately